Coupling the recombineering to Cre-lox system enables simplified large-scale genome deletion in Lactobacillus casei - Yongping Xin; Tingting Guo; Yingli Mu; Jian Kong (Microbial Cell Factories, 2018)
Abstract Background Lactobacillus casei is widely used in the dairy and pharmaceutical industries and a promising candidate for use as cell factories. Recently, genome sequencing and functional genomics provide the possibility for reducing L. casei genome. However, it was still limited by the inefficient and laborious genome deletion methods. Results Here, we proposed a genome minimization strategy based on LCABL_13040-50-60 recombineering and Cre-lox site-specific recombination system in L. casei. The LCABL_13040-50-60 recombineering system was used to introduce two lox sites (lox66 and lox71) into 5′ and 3′ ends of the targeted region. Subsequently, the targeted region was excised by Cre recombinase. The robustness of the strategy was demonstrated by single-deletion of a nonessential ~ 39.3 kb or an important ~ 12.8 kb region and simultaneous deletion of two non-continuous genome regions (5.2 and 6.6 kb) with 100% efficiency. Furthermore, a cyclical application of this strategy generated a double-deletion mutant of which 1.68% of the chromosome was sequentially excised. Moreover, biological features (including growth rate, electroporation efficiency, cell morphology or heterologous protein productivity) of these mutants were characterized. Conclusions To our knowledge, this strategy is the first instance of sequential deletion of large-scale genome regions in L. casei. We expected this efficient and inexpensive tool can help for rapid genome streamlining and generation restructured L. casei strains used as cell factories.